PENGARUH SELF ESTEEM, BUDGET EMPHASIS, DAN LOCUS OF CONTROL TERHADAP BUDGETARY SLACK (STUDI EMPIRIS PADA APARATUR ORGANISASI PERANGKAT DAERAH DI KOTA PALANGKA RAYA) - Maria Febiola Agustina; Hamun S Masin; Yesika Yanuarisa (Universitas Palangka Raya, 2020)
This study aims to determine the effect of self esteem, budget emphasis, and locus of control on budgetary slack. This study uses a quantitative method with a questionnaire as an instrument. The population in this study were all apparatus of the Regional Apparatus Organization (OPD) in the City of Palangka Raya. Based on the purposive sampling method, the number of samples obtained was 100 people. The theory used in this research is agency theory. And the type of research in this study is quantitative research with multiple regression testing and validity and reliability testing is performed to determine the quality of the questionnaire used with the help of SPSS 25 software. The results of this study indicate that partially self esteem and budget emphasis variables have positive and significant effects on budgetary slack. While the locus of control has a positive effect on budgetary slack.